Digital Security in the 4.0 Era: Countering Cyber Attacks on Sharia Financial Institutions - Daffandi, Chandra Ray (Maliki Interdisciplinary Journal, 2025)
The Industrial Revolution 4.0 era brings technological advancements along with new challenges such as cyberattacks on Islamic financial institutions. Threats like phishing, malware, and ransomware endanger customer data and damage public trust. This study explores common cyber threats, their impact on Islamic banking operations, and mitigation efforts. Strategic approaches include encryption, two-factor authentication, firewalls, customer education, and risk management based on ISO 31000:2018. Collaboration with regulatory authorities is also key to building a robust and trustworthy digital security system.